Wood Density of Lower Stratum Trees in a Semi-Deciduous Tropical Forest of Cameroon - Flore, Ntonmen Yonkeu Amandine; Louis, Zapfack; Cedric, Chimi Djomo; Roger, Kabelong Banoho Louis-Paul; Nfornkah, Barnabas Neba; Ingrid, Tsopmejio Temfack; D’Estaing, Nanfack Arsel; Guylene, Ngoukwa; Mireil, Tchoupou Votio; Leocadie, Inimbock Sorel; Nadege, Madountsap Tagnang; Hubert, Mounmemi Kpoumie; et al. (Journal of Forests, 2021)
The lower forest stratum is often neglected in trees wood density studies. The aim of this study was to investigate wood density of lower stratum forest in a semi-deciduous rain forest of Cameroon. The data was collected from 30 random squares plots of 100m² and 200m. The wood density was assessed using immersion method. Wood samples were collected at three levels including: the base, the trunk and branches of trees. Measurement variables collected include the diameter, height and crown diameter. These variables were correlated to wood density using the Pearson coefficient. A total of 1498 samples from 136 tree species were collected. The wood density from these samples varied from 0.156 g.cm-³ to 0.914 g.cm-³, with an average of 0.561 g.cm-³. ANOVA test showed that, wood density decreased significantly from 0.609 to 0.571 and then to 0.509 g.cm-³ for the base, trunk and branches respectively. Interspecific analysis showed that wood density was significantly different between species (ANOVA, p˂0.001). With respect of biological type, the mean wood density of 27 understory tree species (exclusively) found was 0.562 g.cm-³. Wood density of 56 tropical forest tree species hitherto unknown in the literature were determined. The Pearson correlation between measurement variables and wood density was close to zero; nevertheless, it varied in function of the tree species. This study suggested that more investigations of wood density of tropical forest trees should be conducted, particularly in the Congo Basin forests where an important diversity of medium and lower forest stratum trees is expected.